Isolated cilioretinal artery occlusion secondary to perinuclear antineutrophil cytoplasmic antibody vasculitis. Issue 5 (September 2020) - Mammo, Danny A; McClelland, Collin M; Chen, John; Adams, Matthew K; Pulido, Jose; Davies, John B
Introduction: Antineutrophil cytoplasm antibody-associated vasculitides encompass a diverse spectrum of autoimmune diseases characterized by necrotizing small vessel vasculitis. Ocular manifestations may be the presenting findings of antineutrophil cytoplasm antibody-associated vasculitides. Methods: Single, retrospective case study. Results: We report the rare case of a 55-year-old woman with a cilioretinal artery occlusion as the presenting feature of perinuclear antineutrophil cytoplasm antibody-associated microscopic polyangiitis. Conclusions: Although rare, antineutrophil cytoplasm antibody-related vasculitis should be considered in any retinal vascular occlusion, particularly in the setting of patients with new vague headaches and a paucity of vasculopathic risk factors.